The influence of financial management and governance in the provision of social services in non-profit organizations - Oliveira, Márcio (2021)
The financial crises and the pandemic COVID 19 have reinforce the importance of the nonprofit organizations (NPOs) in promoting the social welfare. These institutions face nowadays various challenges related to the new needs required by the populations, and also the deepening of the traditional social problems. In this context, fulfill their social mission implies that NPOs have to take care with their performance and simultaneously maximize the social value generated. The review of the literature allowed to identify factors associated with financial management and governance that may contribute to the definition of the social services offered by NPOs. Thus, in a studied applied to Holy Houses of Mercy in Portugal, this investigation intends to understand the influence of the financial management and the governance on the NPO social services provided. The results obtained show a positive contribution of the finances and the governance on the social services of these institutions, which lead us to conclude that to be more effective in the social services provision, NPOs must emphasize their financial management and governance practices.